Variability of performance of wound infusion catheters. (13th February 2013) - Hansen, Bernie; Lascelles, B Duncan X; Thomson, Andrea; DePuy, Venita
Abstract Objective To compare the distribution of flow from two commercial and one handmade multihole wound infusion catheters. Study design Open label experimental measurement of flow distribution in a bench top apparatus of handmade (n = 10) and two commercial (n = 10 each) wound infusion catheters with 5–6″ (12–15.2 cm) long diffusion surfaces. Methods The distribution of 6 mL of distilled water injected at three different injection speeds (0.5, 5, and 120 minutes) through individual triangular pieces of felt cloth fitted over six contiguous regions of the diffusion surface of each catheter was measured in triplicate. Results The distribution of flow through the six regions was significantly more uniform at the two faster injection speeds. Ninety two per cent of the 120 minute infusion trials resulted in one or more regions producing negligible flow (<5% of total output), and in 16% of the 120 minute trials all the flow came from just one or two regions. Conclusions Constant‐rate infusions of 3 mL hour−1 provide erratic distribution of flow from wound infusion catheters in a bench top apparatus. Commercial catheters did not outperform handmade catheters. Clinical relevance Uneven distribution of flow at low infusion speeds may contribute to inconsistent or unsatisfactory pain relief in patients treated with continuous wound infusions of local anesthetics.